Metformin use in pregnancy - Hernández Castro, Flavio (2015)
Metformin therapy in gestational diabetes (GD) has beneficial effects on insulin resistance and does not appear to be teratogenic; but the use effect in early pregnancy on pernatal morbility has not beenstudied. Objective: To assess that metformin therapy initiated early in pregnancy in obese women with GD reduces macrosomia and neonatl morbidity. Design: Department of Maternal Fetal Medicine, high specialty medical university, Social Security Mexican Institute. Participants: Patients with diagnosis of GD. Interventions: We examined the record of women with GD, 17 or less weeks of pregnancy and a body mass index equal or more than 30 when they started therapy. They were divided in two groups: metformin group (women treated only with metformin throughout pregnancy because they did not accept to use insulin, n = 34) and insulin group (women who received only insulin treatment, n = 40). Perinatal outcomes, mode of delivery, development of gestational hypertension and type 2 diabetes were assessed. Main outcome measures: Perinatal results, birth type, association with hypertensive states and progression to type 2 diabetes in the postpartum. Results: There was a decrease in macrosomia in the metformin group, 1 (2%) vs. 6 (15%) in the insulin group, but this difference was not significant (p > 0,05). Results in neonatal morbidity and gestational hypertension and type 2 diabetes development were similar. Conclusions: Even though results with metformin therapy were not statistically better, it represents a safe management alternative in patients with GD and obesity who do not accept insulin use.